Trends in the Malaysian industrial market structures - Md. Nor, Nor Ghani; Osman, Zulkifly; Abdullah, Ahmad Zainuddin; Chin, Yit Jun (Penerbit Universiti Kebangsaan Malaysia, 2000)
The manufacturing sector currently accounts for more than one third of the nation's output and more than one half of total exports. Unfortunately, little is known about the long run trends in market structure variables in this sector even though, according to economic theory, these variables do say a lot about the short and long run competitive and efficiency conditions of an industry. Knowledge in this area will also enable one to assess the future prospect of Malaysian manufacturing industry in facing greater market liberalization and globalization. This paper shows that the Malaysian industrial market structure had been evolving and that there were indeed some significant trends in several market structure variables.